2018
DOI: 10.2741/s505
|View full text |Cite
|
Sign up to set email alerts
|

The evolving concept of the intrinsic hippocampal theta gamma oscillator

Abstract: Three main types of electrical oscillations are recorded from the hippocampus : theta (θ), gamma (γ) and sharp wave ripples with frequency bands of 4-12, 25-100 and 110-250 Hz, respectively. Theta activity is the more robust of them, and has important physiological roles because it is involved in spatial navigation, memory formation and memory retrieval. Classical lesion studies have suggested that the hippocampus passively follows the θ  rhythm generated in the septum by neurons that are synaptically connecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…In our model, “L1” is ordinarily silent and is disinhibited by activity from an external Unit, oscillating with a theta period. Although recent data suggest that a theta rhythm can also be internally generated within hippocampal circuits ( Cataldi and Vigliotti, 2018 ), as done in our previous model, or modulated by other hippocampal structures such as the entorhinal cortex ( Schlesiger et al, 2015 ), a more common idea is that the theta rhythm originates from an external structure: this may be the septum ( Salib et al, 2019 ), or a resonance within the Papez circuit (including the mammillary bodies, the mammillothalamic tract, and the anterior thalamic nuclei; Vertes et al, 2001 ; Dillingham et al, 2021 ). In particular, Salib et al (2019) suggest that the septum can act by disinhibiting the hippocampus with a mechanism analogous to the one included in our model.…”
Section: Discussionmentioning
confidence: 99%
“…In our model, “L1” is ordinarily silent and is disinhibited by activity from an external Unit, oscillating with a theta period. Although recent data suggest that a theta rhythm can also be internally generated within hippocampal circuits ( Cataldi and Vigliotti, 2018 ), as done in our previous model, or modulated by other hippocampal structures such as the entorhinal cortex ( Schlesiger et al, 2015 ), a more common idea is that the theta rhythm originates from an external structure: this may be the septum ( Salib et al, 2019 ), or a resonance within the Papez circuit (including the mammillary bodies, the mammillothalamic tract, and the anterior thalamic nuclei; Vertes et al, 2001 ; Dillingham et al, 2021 ). In particular, Salib et al (2019) suggest that the septum can act by disinhibiting the hippocampus with a mechanism analogous to the one included in our model.…”
Section: Discussionmentioning
confidence: 99%
“…Different brain regions are involved in generation of the gamma rhythm (Whittington et al., 2011 ). In fact, all mechanisms responsible for the components of EEG spectra and their functional interrelations are still poorly understood (Cataldi & Vigliotti, 2018 ; Jing et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…A more traditional hypothesis is that the theta rhythm is generated in the septum, which possibly acts as a pacemaker for theta activity (Pignatelli et al 2012) and from there is transmitted to hippocampal neurons (Roux and Uhlhaas 2014). However, more recent data have shown that oscillations in the theta range can be recorded in hippocampal preparations in vitro, thus confirming that the hippocampus itself can act as a theta oscillator (Cataldi and Vigliotti 2018).…”
Section: Basic Model Assumptions and Layersmentioning
confidence: 99%